Design and process of the EMA Cohort Study: the value of antenatal education in childbirth and breastfeeding - de la Hera Amaia; Hermosilla Itziar; de Gamboa Gurutze; Grandes Gonzalo; Pinedo Isabel; Paz-Pascual Carmen; Gordon Janire; Garcia Guadalupe; de Pedro Magdalena (BMC, 2008)
Abstract Background Antenatal education (AE) started more than 30 years ago with the purpose of decreasing pain during childbirth. Epidural anaesthesia has achieved this objective, and the value of AE is therefore currently questioned. This article describes the protocol and process of a study designed to assess AE results today. Methods/Design A prospective study was designed in which a cohort of 616 nulliparous pregnant women attending midwife offices of the Basque Health Service were followed for 13 months. Three exposure groups were considered based on the number of AE sessions attended: (a) women attending no session, (b) women attending 1 to 4, and (c) women attending 5 or more sessions. Sociodemographic, personality, and outcome variables related to childbirth and breastfeeding were measured. It was expected 40% of pregnant women not to have participated in any AE session. However, 93% had attended at least one session. This low exposure variability decreased statistical power of the study as compared to the initially planned power. Despite this, there was a greater than 80% power for detecting as significant differences between exposure groups of, for instance, 10% in continuation of breastfeeding at one and a half months and in visits for false labour. Women attending more sessions were seen to have a mean higher age and educational level, and to belong to a higher socioeconomic group (p < 0.01). Follow-up was completed in 99% of participants. Discussion Adequate prior estimation of variability in the exposure under study is essential for designing cohort studies. Sociodemographic characteristics may play a confounding role in studies assessing AE and should be controlled in design and analyses. Quality control during the study process and continued collaboration from both public system midwives and eligible pregnant women resulted in a negligible loss rate.